Immunogenicity and safety of a COVID-19 DNA vaccine in healthy adults and elderly: A randomized, observer-blind, placebo-controlled phase 2 trial - Siyue Jia; Chengwei Shao; Xin Cheng; Hongxing Pan; Zhijian Wang; Yu Xia; Jianfang Xu; Xuefen Huai; Danjing Leng; Jiarong Wang; Gan Zhao; Bin Wang; et al. (Human Vaccines & Immunotherapeutics)
INO-4800 represents a DNA-based vaccine encoding the spike protein of SARS-CoV-2. This phase 2 trial evaluated the immunogenicity and safety of INO-4800 as a primary vaccination series in adults. We conducted a randomized, observer-blind, placebo-controlled phase 2 trial of intradermal injection of INO-4800 in both healthy adults and elderly individuals. Eligible participants from each age group were enrolled and randomly assigned in a 3:3:2 ratio to receive two doses of INO-4800 (1.0 mg or 2.0 mg) or placebo, followed by electroporation on day 0 and day 28. The primary immunogenicity endpoints focused on determining the geometric mean titers (GMTs) of spike-binding antibodies and live SARS-CoV-2 neutralizing antibody at day 30 after the second dose. The primary endpoint for safety was the occurrence of adverse events within 30 days after vaccination. A total of 781 volunteers were recruited and screened for eligibility, with 320 eligible young adults (≥18 to <60 years old) and 320 elderly (≥60 to ≤85 years old) were randomly assigned to receive the low-dose (1.0 mg, n = 120) or high-dose (2.0 mg, n = 120) INO-4800, or placebo (n = 80). Notably, both dose groups exhibited significant increases in spike-binding antibodies at day 30 after the second dose, with GMTs of 1609.3 (95% CI: 1385.5–1869.3) for the low-dose group and 3016.7 (95% CI: 2577.4–3530.8) for the high-dose group. Additionally, both dose groups induced neutralizing antibodies against live SARS-CoV-2, with GMTs of 4.7 (95% CI: 4.2–5.3) and 6.6 (95% CI: 5.9–7.4) at day 30 after the second dose. The incidence of adverse events within 30 days after vaccination was slightly higher in the high-dose group (115 [47.9%]) than that in the low-dose group (105 [43.8%]) (p = .0060). All adverse reactions were grade 1 or 2, primarily occurring within 14 days after vaccination. No vaccine-related serious adverse events were reported. The COVID-19 DNA vaccine INO-4800 at two doses (1.0 mg or 2.0 mg) showed an acceptable safety profile and modest immunogenicity, with the high-dose slightly more immunogenic than the low-dose.Clinical Trials Registration: www.chictr.org.cn, identifier is ChiCTR2000040146.